The Ukrainian Bandura as a Musical Instrument of the Chordophone Group - Dutchak, Violetta (Journal of Vasyl Stefanyk Precarpathian National University, 2017)
The article examines the characteristics of the bandura as a plucked chordophone. A comparative analysis of the researches undertaken by outstanding musicologists, performers, ethno-organologists S. Lyudkevych, E. Hornbostel, C. Sachs, H. Khotkevych, Z. Shtokalko, and others is carried out. The morphology of the instrument and the main stages in its evolution are discussed. The stable and mobile elements of the bandura’s structure and tuning are described. The technical characteristics of the instrument in different periods of its evolution and the achievements of the bandura makers and bandurists of Ukraine and the Ukrainian diaspora are analyzed. The common and distinguishing features of the bandura and some kindred instruments are pointed out